Empirical political analysis quantitative and qualitative research methods - Rich, Richard C. (Routledge, Taylor & Francis Group, 2018)
Empirical Political Analysis introduces readers to the foundations of social science research. Organized around the stages of the research process, this textbook prepares readers to conduct both quantitative and qualitative research, from the formation of theory through the design of research projects, to the collection of data and the analysis of results. It offers a clear and concise presentation of basic concepts and tools that can be applied in a wide range of research settings and highlights ethical conduct in the research process. It will help you both to achieve sound results in your own research and to critically evaluate research presented by others.